Mortality due to fracture of the proximal femur: a systematic review (Research, Society and Development, 2022)
Introduction: Proximal femur fractures can occur in people of all ages. However, they are more commonly found in people of older age, even more frequently in women over 60 years. These fractures can be considered surgical emergencies and may aggravate by the presence of comorbidities. Patients who present this type of fracture showed an increased mortality rate, associated with general conditions of this individual as age and patient physiology. Objective: To verify the scientific evidence related to deaths caused by proximal femoral fractures in the general population. Methodology: This is a descriptive, qualitative, systematic literature review study. For article research, PubMed/Medline and Scielo database platforms were chosen. All articles published in the last ten years (2012-2022) were included. The following descriptors were used: "fracture of the proximal femur", "deaths" and "impacts". Results and Conclusion: A total of ten articles indexed in the Scielo®, MedLine®, and PubMed® databases from 2004 to 2021 were found. Through this systematic review, the length of hospitalization was correlated to the patient's gender and comorbidities. This analysis pointed out that a longer exposure to the hospital environment, associated with comorbidities, may be a factor that leads to increased mortality in these patients.